Geochemical fractionation of trace elements in the coral reef sediments of the Lakshadweep Archipelago, Indian Ocean. (September 2020) - Joy, Anu; Anoop, P.P.; Rajesh, R.; Mathew, Jose; Mathew, Angel; Gopinath, Anu
Abstract: Geochemical fractionation of seven trace elements (Cr, Mn, Fe, Cu, Zn, Cd, and Pb) was investigated in the surficial coral reef sediments of three inhabited islands (Kavaratti, Kadmat, and Agatti) belonging to the Lakshadweep Archipelago. The observations indicated that the metals showed their highest contents in the residual fraction of geological origin. The extent of risk, bioavailability, and contamination of trace elements was assessed by risk assessment codes and contamination factors. Based on the results, medium potential adverse effects were observed in the sediments of Kavaratti and Agatti. The concentration of Cd in the exchangeable and carbonate-bound fractions was above its global average shale value in the sediments of Kavaratti and Agatti, suggesting its high mobility and bioavailability and thus an environmental threat to the coral reef ecosystem. Highlights: First report on metal fractionation in the coral reef sediments of Lakshadweep Residual phase of geological origin was the major fraction of trace elements. Based on risk assessment code values, cadmium, lead, zinc and copper showed medium risk. Medium potential adverse effects were observed in Kavaratti and Agatti. Cadmium was identified as the dominant pollutant in Lakshadweep.